Vascular covered stent and video-assisted thoracoscopic surgery for Aortoesophageal fistula caused by esophageal fishbone: a case report - Jianfeng Chen (Journal of Cardiothoracic Surgery, 2024)
Abstract Background Aortoesophageal fistula (AEF) is a rare condition characterized by communication between the aorta and esophagus. AEF caused by an esophageal foreign body is even rare, and there is currently no recommended standard treatment protocol. We report a case of delayed aortic rupture after the endoscopic removal of a fish bone, which was successfully treated with a combined approach of vascular stenting and thoracic surgery. Case presentation A 33-year-old man presented to the hospital after experiencing chest discomfort for 3 days following the accidental ingestion of a fish bone. Under endoscopic guidance, the fish bone was successfully removed, and the patient was subsequently admitted for medical therapy. On the fourth postoperative day, the patient suddenly developed hematemesis, and chest computed tomography angiography revealed the presence of an AEF. This necessitated urgent intervention; hence, thoracic surgery was performed and a vascular-covered stent was placed. Following the surgical procedure, the patient received active medical treatment, recovered well, and was successfully discharged from the hospital. Conclusions In patients with esophageal perforation caused by foreign bodies, hospitalization for observation, computed tomography angiography examination, early use of antibiotics, and careful assessment of aortic damage are advised. Thoracic endovascular aortic repair and esophageal rupture repair may have benefits for the treatment of AEF.